Air quality impact due to scrap-metal handling on a sea port: A wind tunnel experiment - Borrego, C. (2007)
Emissions from cargo unloading and handling activities in sea ports can be of special importance, particularly in case of proximity to dense urban populations. In this sense, the main purpose of this work was to develop and implement a set of technical solutions intended to reduce the emissions and dispersion of particles resulting from scrap-metal handling on one of the most important Portuguese sea ports. The analysis of the atmospheric flow within the discharging berth was carried out in the Wind Tunnel Laboratory of the Department of Environment and Planning, at the University of Aveiro (Portugal). Laser sheet and hot wire anemometry techniques were applied. Two possible solutions were proposed, consisting in the use of windbreaks located upwind of the scrap-metal piles and a barrier of containers positioned downwind. Both flow visualisation and velocity-measuring techniques confirm a higher efficiency in the reduction of suspended particulate matter by using the containers plus the windbreaks. This combined solution is responsible for an important reduction on the emissions from the scrap-metal piles under typical meteorological conditions for this area, offering a good compromise between cost, time needed for implementation and efficiency.